(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
The rollout of 5G networks is gaining momentum rapidly around the globe, and it holds the promise of delivering incredibly high data transfer rates, minimal latency, and huge interconnectedness. This article provides an overview of 5G networks, including a discussion of the technology, applications, and issues involved. First, we will discuss the technical features of 5G networks. These aspects include the spectrum, radio access methods, network design, and upcoming technologies such as network slicing and edge computing. After that, we will talk about a variety of applications, such as the Internet of Things, virtual reality, and autonomous cars, that have the potential to benefit from the capabilities of 5G networks. In conclusion, we investigate the primary obstacles that need to be conquered in order to fully fulfil the potential of 5G networks. These obstacles include concerns over regulation, privacy, and security. In addition, we give an overview of the present state of 5G networks and finish up with potential future research and development possibilities. The study is based on a survey of the relevant literature, and its primary objective is to deliver a full comprehension of the current state of the art regarding 5G networks.